Prevalence, impact and molecular characterisation of parasites in harbour porpoises and harbour seals - Lehnert, Kristina (2009)
Parasitism is ubiquitous in wildlife, but little is known about the dynamics of parasitic infections and associated diseases in marine mammals. This thesis aimed to characterise the parasite fauna of harbour porpoises (Phocoena phocoena) and harbour seals (Phoca vitulina) to assess the impact on their health status and to improve the knowledge about the life history of their lungworm species. Parasitological investigations were carried out on harbour porpoises originating from the German North and Baltic Seas and the Norwegian North Sea. The parasites found in porpoises originated mainly from the respiratory tract and comprised four pseudaliid nematodes (Pseudalius inflexus, Torynurus convolutus, Halocercus invaginatus, Stenurus minor), one ascaridoid nematode (Anisakis simplex) and two trematodes (Campula oblonga, Pholeter gastrophilus). The finding of H. invaginatus was the first geographic record from German waters. Differences were found in the severity of the parasitic infection between stranded and bycaught animals as well as between porpoises from different areas. A correlation was shown between parasitic infection and observed lesions. Lungworm prevalence and intensity of infections increased with age suggesting horizontal transmission through the food web. The data also indicated that infections were accumulated with age and long‐lived. The occurrence of whale‐lice, Isocyamus delphinii (Crustacea: Amphipoda: Cyamidae), infestation was described in a stranded harbour porpoise. The emaciated animal had multiple, partially scarred wounds to which numerous small crustaceans were attached. The whale‐lice showed a significant sexual dimorphism and their population was male biased. The lesions in the lung were found to be the likely cause of death in this porpoise, and the ectoparasites were not diagnosed to be a major health threat to the animal. The skin wounds’ origin remained unclear, but the lice seemed to be closely associated and dependent on the wounds of this host. In this first and unusual occurrence ...